Efektivitas Dukungan Swabantu (Self Help Group) Dalam meningkatkan Kepatuhan dan Kualitas Hidup Pasien Tuberkulosis : Tinjauan Sistematik - Puspitasari, Iis; Permatasari, Henny; Nursasi, Astuti Yuni; Widyatuti, Widyatuti (Jurnal Kesehatan Komunitas, 2025)
Tuberculosis (TB) remains a major global health challenge, especially in countries with high disease burdens like Indonesia. Treatment non-adherence and reduced quality of life among TB patients continue to undermine control efforts. This systematic review seeks to explore how self-help group (SHG) interventions contribute to enhancing medication adherence and improving the quality of life (QoL) among individuals living with TB. A systematic review was followed the 2020 PRISMA guidelines. Comprehensive searches were performed across PubMed, Science Direct, ProQuest, Scopus, and Google Scholar using the PICO framework. Studies of various designs (RCTs, cohort, quasi-experimental, and cross-sectional) involving TB patients receiving SHG interventions were included. Eight eligible studies were critically appraised using the JBI checklist. Despite differences in design, participants, and SHG approaches such as patient education, motivation, emotional support, behavioral empowerment, and digital integration the studies consistently showed improvements in medication adherence and quality of life, supported by generally strong methodological quality. The findings highlight the importance of structured SHG models in nursing practice, supporting the development of community-based interventions and protocols that enhance TB treatment outcomes and patient well-being. Future studies should prioritize robust RCTs with diverse populations and long-term follow-up, including hybrid models that integrate digital technologies to ensure sustainable implementation in high-burden settings.